Smart smoke ventilation and power generation (SSVPG) - Ismail, Daut, Prof. Dr.; Shasidharan, Gomesh Nair; Muhammad Irwanto; Mohd Irwan, Yusoff; Muhammad Fitra, Zambak (Korea Invention News, 2013)
Cyber International Genius Inventor Fair (CIGIF) 2012, 3rd - 9th November 2012 was held at ChungMu Art Hall Convention Centre, Seoul, Korea.